Kinetics of enzymatic synthesis of liquid wax ester from oleic acid and oleyl alcohol - Radzi S.M.; Mohamad R.; Basri M.; Salleh A.B.; Ariff A.; Rahman M.B.A.; Abdul Rahman R.N.Z.R. (Japan Oil Chemists Society, 2024)
Indexed by WOS/ Scopus